Some Interesting Plants from West Bengal - Vuppuluri, Sharma S. (Indian Forester, 1969)
During studies on the Weed-flora of the Indian Botanic Garden, Shibpur, Howrah (W. Bengal), some interesting plants were met with. Indigofera spicata Forsk. I has been collected for the first time from Bengal. Detailed description with illustrations is given for the hitherto little known Melochia pyramidata Linn., along with a key to its identity. Oxalis martiana Zucc., an introduction from S. America, was met with in wild state. Turnera subulata J.E. Smith was also observed as growing wild in the garden.